Sustainability Implementation in Romanian Tourism: From the Paris Agreement to Electric Up - Viorel Mionel; Adrian Lucian Kanovici; Alexandru Gavriș; Oana Mionel; Marius Cristian Neacșu; Claudia Popescu (Amfiteatru Economic, 2024)
Rising energy prices and the commitments made under the Paris Agreement have prompted Romanian tourism companies to reconsider implementing sustainable practices and technologies. The Electric Up programme stands out as an essential tool in this regard, contributing to the reduction of greenhouse gas emissions, increasing the attractiveness of tourism, and stimulating the local economy. Our study analyses the impact of the Electric Up programme by correlating data on beneficiaries, tourist arrivals, and energy consumption. The results show that counties with high solar potential and developed tourist infrastructure have benefited the most from the programme. Harnessing solar potential, equitable distribution of funds, and promoting the programme in under-represented regions are key elements to maximising its positive impact and achieving Romania's sustainability goals.